Video and Audio for Designers with Creative Cloud: Part 1. - Harmer, Tony (linkedin.com, 2017)
Learn how to use Creative Cloud for video and audio production. Discover how to leverage existing visual design skills to grasp the fundamentals of working with motion and sound.